Developmental changes of lymphoid tissue in Harderian gland of the laying hens - Pamela Bejdić; Rizah Avdić; Ljiljana Amidžić; Velida Ćutahija; Faruk Tandir; Nedžad Hadžiomerović (Macedonian Veterinary Review, 2014)
The Harderian gland of 110 laying hens was histologically investigated from the time of hatching to the period of 10 months of age. Tissue sections were stained with haematoxylin and eosin, periodic acid-schiff (PAS) and methyl green-pyronin technique. The research shows that lymphoid tissue is colonised by three types of cells: heterophils, lymphocytes and plasma cells. The number of these cells is directly dependent on bird’s age. During the lifetime of the hens there gradually comes a shift in dominance of these three cell types. Lymphoid nodules are detected only in 40-day-old chickens, while later in adult birds Harderian gland is the organ which contain the largest number of mature plasma cells. Some plasma cells contain the Russell bodies with different size and shape.